Are the Sustainable Development Goals Realistic and Effective: A Qualitative Analysis of Key Informant Opinions - Mathers, Annalise; Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2018)
The UN Sustainable Development Goals (SDGs) were devised in part to help define the international development funding agenda for future decades. This study sought to explore the challenges and strengths of the SDGs, with respect to their ability to effectively address current and future global health issues. Active researchers and opinion leaders in global health research were interviewed about their opinions on the future of global health, with particular attention to the likely impact of the SDGs on individual research programs. According to thematic analysis, respondent felt that the SDGs should focus more on the development of good governance structures, address corruption and tax systems to develop more comprehensive health structures and financing and embody a more holistic approach to global health.
Keywords: Global health; International development; international health; Millennium Development Goals; Sustainable Development Goals; United Nations